Development of Alternative Energy Digital Teaching Material Integrated PBL Model with Canva to Promote Students’ Critical Thinking Skills - Hanifah, Hanifah; Asrizal, Asrizal; Ulmi, Fauziah; N, Annisa; Ashel, Hazrati (Journal of Innovative Physics Teaching, 2025)
Critical thinking is a crucial 21st-century skill that students need to develop. However, initial studies indicate that students' critical thinking skills are still relatively low. This study aimed to develop digital teaching materials integrated with the Problem-Based Learning (PBL) model that are both valid and practical to improve students' critical thinking abilities. The research followed a Research and Development (R&D) design using the Hannafin and Peck development model. The development process reached the limited trial stage, conducted with Grade X students. Data were collected through expert validation sheets and student practicality questionnaires. Descriptive statistical analysis was used to describe the validity and practicality results in the form of tables and graphs. The findings showed that the digital teaching materials were valid and practical. Expert evaluations resulted in an average score of 83.6, indicating excellent validity in content, visual design, instructional design, software functionality, and PBL integration. Students gave an average score of 82.2, reflecting very high practicality in terms of usefulness, ease of use, clarity, appeal, and affordability. Based on these results, the alternative energy-themed digital teaching materials integrated with the PBL model are considered effective for supporting classroom learning and enhancing students' critical thinking skills.